Influence of visual background on discrimination of signal-relevant colours in zebra finches (Taeniopygia guttata). Issue 1976 (8th June 2022) - Davis, Alexander; Zipple, Matthew N.; Diaz, Danae; Peters, Susan; Nowicki, Stephen; Johnsen, Sönke
Abstract : Colour signals of many animals are surrounded by a high-contrast achromatic background, but little is known about the possible function of this arrangement. For both humans and non-human animals, the background colour surrounding a colour stimulus affects the perception of that stimulus, an effect that can influence detection and discrimination of colour signals. Specifically, high colour contrast between the background and two given colour stimuli makes discrimination more difficult. However, it remains unclear how achromatic background contrast affects signal discrimination in non-human animals. Here, we test whether achromatic contrast between signal-relevant colours and an achromatic background affects the ability of zebra finches to discriminate between those colours. Using an odd-one-out paradigm and generalized linear mixed models, we found that higher achromatic contrast with the background, whether positive or negative, decreases the ability of zebra finches to discriminate between target and non-target stimuli. This effect is particularly strong when colour distances are small (less than 4 ΔS) and Michelson achromatic contrast with the background is high (greater than 0.5). We suggest that researchers should consider focal colour patches and their backgrounds as collectively comprising a signal, rather than focusing on solely the focal colour patch itself.